Performance Evaluation of an Air-Conditioning Compressor Part I: Measurement and Design Modeling - Thomas W. Bein; Yu-Tai Lee (International Journal of Rotating Machinery)
In order to comply with legislation to eliminate the use of refrigerants that damage the ozone layer, it is necessary to redesign centrifugal compressors, used by the US Navy for shipboard air-conditioning systems, to use an environmentally acceptable refrigerant. This paper describes an evaluation of a 125-ton compressor designed to use HCFC-124 as the refrigerant. The objectives are not only conducting the performance evaluation, but also pinpointing the design problems for achieving a high-performance compressor. The design method used to design the 125-ton compressor is first reviewed and some related performance curves are predicted based on a quasi-3D method. In addition to an overall performance measurement, a series of instruments were installed on the compressor to identify where the measured performance differs from the predicted performance. The measurement techniques for providing the diagnostic flow parameters are also described briefly. Part II of this paper provides predictions of flow details in the areas of the compressor where there were differences between the measured and predicted performance.